Modified congener analysis: quantification of cyanide in whole blood, other body fluids, and diverse beverages - Sundermann, Tom R.; Schmitt, Georg; Bartel, Marc (Drug testing and analysis, 2021)
The congener analysis is routinely used for the determination of volatile compounds in body fluids and beverages. A modified method to quantify cyanide in whole blood has been developed, validated, a...
First published: 16 September 2020
Gesehen am 06.12.2021